Elucidating stratovolcano construction from volcaniclastic mass‐flow deposits: The medial ring‐plain of Taranaki Volcano, New Zealand. Issue 6 (8th June 2021) - Zemeny, Aliz; Procter, Jonathan; Németh, Károly; Zellmer, Georg F.; Zernack, Anke V.; Cronin, Shane J.
Abstract: Long‐lived stratovolcanoes display a thick volcanic apron surrounding the edifice. This sedimentary succession incorporates the majority of the deposits from both growth and destruction phases of a volcanic massif. The ring plain of Taranaki Volcano (>200 ka) is composed of volcaniclastic mass‐flow deposits that are exceptionally well‐exposed along its coastal‐cliff shoreline, at 20 to 30 km distance from the edifice. Overall, the volcaniclastic deposits in the southern and south‐western sector record three growth phases (65 to 34 ka) which can be investigated due to access and stratigraphic control of the ring‐plain section. Each cyclic growth phase is represented by a sequence of mass‐flow deposits. Lithostratigraphic units or repeated packages with similar properties were identified in order to understand the depositional sequences. The mass‐flow units within these growth phases can be described by three criteria subdivided into nine distinct sedimentological textural types (for example, massive, graded, etc.), five different lithological types (for example, lithic‐dominated, polylithological, etc.) and three main physiographic facies types (sheet, overbank and channel). The mass‐flow deposits can then be further categorized through a classification scheme by assigning these three criteria. Widely distributed lithic‐dominated hyperconcentrated‐flow deposits were recognized, which are thought to be directly or indirectly associated with eruption‐fed events (remobilized from 'block and ash' flows) providing evidence for eruptive activity occurring on a 4 to 10 kyr cycle. Therefore, this study proposes classification criteria for mass‐flow deposits in volcanic ring‐plains using a developed three‐part coding system. The study also aims to clarify the order of sedimentary and volcanic events by establishing a stratigraphic model for the investigated time‐period offering a better understanding for future research.